Toward sustainable food systems: can spirulina (Arthrospira platensis) become a sustainable source of protein to enhance the nutritional benefits of cultured Nile tilapia (Oreochromis niloticus)? - Soma, Katrine; Kals, Jeroen; Opiyo, Mary A.; Ndambi, Asaah; García-Cubero, Rafael; Barbosa, Maria J.; Rurangwa, Eugene; Vernooij, Adriaan (Frontiers in Sustainable Food Systems, 2024)
Hunger affected 278 million people in Africa in 2021, and in Kenya, the proportion of the population unable to afford a healthy diet is 81%. To combat hunger and increase resilience throughout the food system, spirulina (Arthrospira platensis) has been shown to have remarkable properties. The main aim of this study is to investigate whether protein from spirulina is a suitable alternative to protein sourced from fish meal in fish feed for juvenile Nile tilapia (Oreochromis niloticus). In a trial investigating the use of spirulina biomass for fish feed on juvenile Nile tilapia, it has been proven that tilapia fingerlings fed diets with spirulina, replacing up to 30% of fish meal protein, were not affected in terms of growth performance compared to the fish fed the commercial diet. This shows that, nutritionally, protein from spirulina can replace fish meal protein fed to juvenile Nile tilapia. This offers promising opportunities for enhanced food and nutrition security. If produced affordably, spirulina can have a significant impact on the income level of low-income fish farmers in Kenya, who often spend more than 50% of their income on commercial fish feed. Affordability can be made possible if small-scale farmers can produce spirulina using animal manure that is available on the farm instead of using highly priced commercial fertilizer. The additional environmental benefits of spirulina include carbon dioxide sequestration and the removal of nitrogenous and phosphorous waste from the wastewater. Spirulina can therefore increase the sustainability of a whole food system.